Theoretical approaches to biological control - Hawkins, Bradford A.; Cornell, Howard Vernon 1947- (Cambridge University Press, 1999)
Biological control is the suppression of pest populations using predators, parasitoids and pathogens. Historically, biological control has largely been on a trial-and-error basis, and has failed more often than it has succeeded. However by developing theories based upon fundamental population principles and the biological characteristics of the pest and agent, we can gain a much better understanding of when and how to use biological control. This book gathers together recent theoretical developments and provides a balanced guide to the important issues that need to be considered in applying ecological theory to biological control. It will be a source of productive and stimulating thought for all those interested in pest management, theoretical ecology and population biology
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Mathematisches Modell; Pests / Biological control; Insect pests / Biological control; Pests / Biological control / Mathematical models; Insect pests / Biological control / Mathematical models; Biological pest control agents; Biologische Schädlingsbekämpfung; Insekten; Ökologie; Theorie; Theoretische Biologie; Aufsatzsammlung